EKOLOGI TEGAKAN HUTAN TEMBAWANG DUSUN MANGGAM BATI KUALA BEHE KABUPATEN LANDAK PROVINSI KALIMANTAN BARAT - Jekso, Pianus; Lumangkun, Augustine (JURNAL HUTAN LESTARI, 2018)
Tembawang is a forest land managemen system performed by local people of West Kalimantan and has unique ecosytem which has high value of economy, bio-diversity and high conservation in that area is used by local people. Howere, its ecosystem has now changed drastically, plantation, and excessive use of tembawang forest, leading to lost of various vegatation in that area. The research aimed to find out dominan vegetation in Tembawang forest. The research was conducted in Tembawang forest in dusun Manggam Bati Kuala Behe of Landak district. Surve was used as a method of the research. The research analyzed types of seedlings, sapling, poles, tree stage growing in Tembawang forest. The research finding showed  that the Tembawang forest is dominated by trees with criteria for seedling, saplings and poles, and tree stage. The composition of species  in Tembawang forest is dominanted by durian (Hevea brasiliensis) for sapling and poles with important Value Index (IVI= 156.52%) rubber (Hevea brasiliensis) foe sapling and poles with important Value Index - 126.32% and 533.57% respectively and (Durio zibethinus) for stage with Importan Value Index 174.74%.Keywords: biodiversity, ecology, forest, stand, tembawang